2004
DOI: 10.1023/b:jach.0000042677.89276.10
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Surface Modification of Aluminium Sheets for Application to Nano-electronic Devices: Anodization Aluminium and Electrodeposition of Cobalt-Copper

Abstract: A nano-porous anodized aluminum oxide layer was synthesized on the surface of bulk aluminum at a wide range of anodization voltages. The barrier layer at the pore bottom of anodized aluminum oxide layer was chemically etched to make good electrical contact for nanowires electrodeposited in the pores thus formed on metallic aluminum substrates.Cathodic polarization was examined at a wide range of cathode potentials to investigate the electrodeposition behavior of Cu and Co into the pores. Co 81 Cu 19 /Cu multil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 16 publications
(13 reference statements)
1
26
0
1
Order By: Relevance
“…As shown in this figure, in the both magnetic field direction, the resistance of CoNi/Cu multilayered nanowires was decreased with increase in magnetic field and 15.8 % of giant magnetoresistance effect was observed in the multilayered nanowires with 3,000 bi-layers of CoNi alloy layer (10nm) and pure Cu layer (10 nm). These results correspond well to our previous reports, in which 20 % of GMR response has been demonstrated using short length Co/Cu multilayered nanowires electrodeposited into anodized aluminum oxide nanochannels with diameter of 60 nm and length of 2 Pm [15][16][17]. Fig.6 Magnetoresistive hysteresis obtained from an array of electrodeposited CoNi/Cu multilayered nanowires with diameter of 60 nm and length of 60 mm.…”
Section: Anodized Aluminum Oxide Nanochannelssupporting
confidence: 91%
See 1 more Smart Citation
“…As shown in this figure, in the both magnetic field direction, the resistance of CoNi/Cu multilayered nanowires was decreased with increase in magnetic field and 15.8 % of giant magnetoresistance effect was observed in the multilayered nanowires with 3,000 bi-layers of CoNi alloy layer (10nm) and pure Cu layer (10 nm). These results correspond well to our previous reports, in which 20 % of GMR response has been demonstrated using short length Co/Cu multilayered nanowires electrodeposited into anodized aluminum oxide nanochannels with diameter of 60 nm and length of 2 Pm [15][16][17]. Fig.6 Magnetoresistive hysteresis obtained from an array of electrodeposited CoNi/Cu multilayered nanowires with diameter of 60 nm and length of 60 mm.…”
Section: Anodized Aluminum Oxide Nanochannelssupporting
confidence: 91%
“…On the other hand, Martin has reported that a metallic nanowire array can be grown by electrodeposition into a template with numerous nanochannels [8]. Ion-track etched polycarbonate membrane filters [9][10][11][12][13] and anodized aluminum oxide membrane filters [14][15][16][17] are known for a typical nanochannel template [18] for growing nanowires. Blondel et al have reported that Co/Cu and Ni-Fe/Cu multilayered nanowires with GMR response can be fabricated [19].…”
Section: Introductionmentioning
confidence: 99%
“…Co/Cu multilayers are grown by electrodeposition in commercial ion-track-etched polycarbonate membranes of 6 mm in thickness [9,10]. The electroplating is performed in the conventional tree electrodes method.…”
Section: Techniquementioning
confidence: 99%
“…Among of them, the array of numerous metallic nanowires with straight shape is the best candidate to be applied for magnetic storage media with high density domain. Metallic nanowires can be synthesized by stretching micro-scale metallic wires down to nano-scale, while the nanowires can be also synthesized by electrodeposition technique using a nano-well template such as an alumite film [1][2][3][4][5][6][7][8]. In 1975, using an anodic oxide coating film on aluminum, magnetic properties of electrodeposited Co nanowires and Co-Ni alloy nanowires were investigated by Kawai & Ueda [9].…”
Section: Introductionmentioning
confidence: 99%